Aromatase inhibitors decrease radiation-induced lung fibrosis: Results of an experimental study. (August 2016) - Altinok, A.Y.; Yildirim, S.; Altug, T.; Sut, N.; Ober, A.; Ozsahin, E.M.; Azria, D.; Bese, N.S.
Abstract: Purpose: In experimental and clinical trials, tamoxifen (TAM) has been shown to increase radiation-induced lung fibrosis (RILF). Furthermore, aromatase inhibitors (AI) have been shown to be superior to TAM in the adjuvant setting and preclinical data suggest that letrozole (LET) sensitizes breast cancer cells to ionizing radiation in other studies. In this experimental study, we evaluated whether AI have any impact on the development of RILF in rats. Materials and methods: 60 female wistar- albino rats were divided into 6 groups: Control (group A), RT alone (group B), RT + TAM (group C), RT + anastrozole (ANA group D), RT + LET (group E), and RT + exemestane (EXE, group F). RT consisted of 30 Gy in 10 fractions to both lungs with an anterior field at 2 cm depth. Equivalent doses for 60 kg adult dose per day of TAM, ANA, LET, and EXE were calculated according to the mean weight of rats and orally administrated with a feeding tube. Percentage of lung with fibrosis was quantified with image analysis of histological sections of the lung. The mean score values were calculated for each group. the significance of the differences among groups were calculated using one way ANOVA test and Tukey HSD post-hoc test. Results: Mean values of fibrosis were 1.7, 5.9, 6.7, 2.5, 2 and 2.2 for groups A, B, C, D, E, and F, respectively (p = 0.000). TAM increased RT-induced lung fibrosis but without statistical significance. Groups treated with RT + AI showed significantly less lung fibrosis than groups treated with RT alone or RT + TAM (p = 0.000). RT + AI groups showed nearly similar RT-induced lung fibrosis than control group. Conclusions: In this study, we found that AI decreased RT-induced lung fibrosis to the control group level suggesting protective effect. Highlights: Effects of concurrent aromatase inhibitor use with radiotherapy investigated. Rats have been irradiated to cause radiation induced lung fibrosis. Aromatase inhibitors decrease radiation induced lung fibrosis scores. Aromatase inhibitors act as radioprotective agents.